Role of HDAC inhibition and environmental condition in altering phases of amphetamine self-administration - Arndt, David L. (Kansas State University, 2016)
Gene-environment interactions play a significant role in drug abuse and addiction. Epigenetics (the study of how environmental stimuli alter gene expression) has gained attention in recent years as a significant contributor to many behavioral phenotypes of drug addiction. The current study sought to determine if differential rearing conditions can alter a specific epigenetic mechanism, histone deacetylase (HDAC), and how HDAC inhibition can affect drug-taking and drug-seeking behaviors differently among enriched, isolated, or standard-housed rats. Ninety male Sprague-Dawley rats were reared for 30 days in enriched (EC), isolated (IC), or standard (SC) conditions prior to amphetamine (0.03, 0.05, 0.1 mg/kg/infusion, i.v.) self-administration, extinction, or reinstatement sessions. Trichostatin A (TsA; 0.3 mg/kg, i.v.), an HDAC inhibitor, was injected 30 min prior to drug-taking or drug-seeking sessions. Results indicated that EC rats self-administered less amphetamine (0.03 mg/kg/infusion) than IC rats. No significant effects of TsA administration were found on general self-administration for any of the three amphetamine doses. While enrichment facilitated the extinction of active lever pressing, there was also a mild facilitation of extinction in IC-TsA rats compared to IC-vehicle counterparts. Lastly, TsA administration decreased cue-, but not drug-induced reinstatement, with IC-TsA rats exhibiting significantly attenuated cue-induced reinstatement compared to IC-vehicle rats. These findings suggest that differential rearing can alter HDAC mechanisms that can change drug-seeking behaviors, particularly in rats reared in isolated conditions. While TsA-induced HDAC inhibition may be less protective against general amphetamine self-administration, it may decrease drug-seeking tendencies during relapse that are induced by the reintroduction of contextual environmental cues heavily associated with drug reward.
Keywords: Behavioral epigenetics; Amphetamine; Self-administration; Histone deacetylase inhibition; Classical conditioning; Operant conditioning